(untitled) (Global Journals of Research in Engineering, 2022)
Everything evolves according to the needs of culture and time. At all times, solutions are created by adding more and more to civil construction. In this context, the Insulated Concrete Forms (ICF) construction method appears as an option for regions with aggressive climate, however, as important as the thermal properties are, the acoustic properties are too since they provide comfort and quality of life for the resident. Thus, the present article aims to carry out a comparative analysis of the acoustic insulation properties between the ICF method and the conventional masonry method through data collection performed by a digital sound level meter while its analysis is performed with the aid of Excel. As it is a work based on the volume of collected data, it has a quantitative nature and as the study target is an underexplores topic and focused on a specific case, it is possible to define that the present work is also a case study of an exploratory nature, being that, after carrying out the experiment, the results indicated that the conventional masonry presented an average Leq reduction superior to the ICF by 8.16% compared to the environment.